Appellate Court Procedures - (:unkn) unknown (My University, 2016)
The current volume seeks to facilitate comparative inquiry by adopting a tabular format. Each tablecovers a central topic and includes all of the appellate courts with relevant jurisdiction or procedures. A portrait ofstructure and procedures for a particular appellate court can be compiled by finding the desired topics in the tableof contents and then locating the court in the appropriate tables.